Synthesis of Gold Nanoparticles Using Pegagan Leaf Extract as Reductor and Tyrosinase Enzyme Inhibitor Activity Test - Indriyani; Suparman; Wiranti Sri Rahayu (Proceedings Series on Health & Medical Sciences, 2026)
Introduction: Nanoparticles ranging from 1-100 nm in diameter can be synthesized using green synthesis methods, which utilize environmentally friendly, non-toxic, economical, and easily manageable resources to promote sustainable nanotechnology development. Pegagan contains saponins, triterpenoids, flavonoids, and tannins that serve as antioxidants for the skin, offering anti-inflammatory and anti-aging benefits. This study aims to synthesize and characterize gold nanoparticles using pegagan leaf extract, and evaluate its potential as an inhibitor of the tyrosinase enzyme involved in melanin formation in human skin. Methods: Synthesis was conducted by mixing HAuCl4 at a concentration of 2 mM with liquid extract of pegagan leaves. The synthesized products were characterized using UV-Vis spectrophotometer, spectrofluorometer, and Particle Size Analyzer to observe the characteristics of the formed nanoparticles. Additionally, the inhibition activity of the tyrosinase enzyme was tested using a microplate reader at a maximum wavelength of 490 nm. Results: During the synthesis of gold nanoparticles, there was a color change in the solution from yellow to purple. Measurements using UV-Vis spectrophotometer showed a spectrum with a peak wavelength at 533 nm, but no fluorescence was observed. Gold nanoparticles measured using PSA ranged in size from 24.36 to 91.28 nm. The inhibition activity test of the CA-AuNPs solution yielded an IC50 of -2,286.202 µg/ml, while the positive control solution using kojic acid showed an IC50 of 31.615 µg/ml. Conclusion: Gold nanoparticles can be synthesized using pegagan extract as a reducer, but they do not exhibit potential as inhibitors of the tyrosinase enzyme.